Factors Affecting Sectio Caesarea Delivery at the Padangsidimpuan City Regional General Hospital - Pulungan, Nikmatul Khoiriyah; Harahap, Meilani; Hasibuan, Ennysah (International Journal of Public Health Excellence (IJPHE), 2022)
Indonesia is one of the countries with the highest maternal mortality rate (MMR) in Asia compared to other ASEAN countries, reaching 359 maternal deaths per 100,000 births. This study aims to determine the Factors Affecting Sectio Caesarea Delivery in Regional General Hospitals Padangsidimpuan City 2018. The research design is an observational analytic study with a case control design and takes 100 respondents, consisting of 50 cases and 50 controls. Data collection was carried out using a check list sheet which was carried out in July 2018. The results of the hypothesis test showed that there was an effect of maternal age (p=0.001; OR 10.5), fetal position abnormalities (p=0.004; OR 9.2), prolonged labor (p=0.005; OR 8.5), premature rupture of membranes ( p=<0.000 OR 23.1), and placenta previa (p=0.001; OR 60.3) with cesarean section delivery and there was no effect of macrosomia (large baby) with cesarean section delivery (p=0.092) in Padangsidimpuan City Hospital. The dominant variable was placenta previa (p=0.001; OR 60.3; 95% CI 5,437-668,215). It is recommended to pregnant women to provide information about sectio caesarea and provide counseling to mothers who check their pregnancy so that mothers better understand risky conditions and can prepare themselves to avoid them.